Nanotwins Strengthening High Thermoelectric Performance Bismuth Antimony Telluride Alloys. Issue 14 (18th March 2022) - Qin, Haixu; Qu, Wanbo; Zhang, Yang; Zhang, Yongsheng; Liu, Zihang; Zhang, Qian; Wu, Haijun; Cai, Wei; Sui, Jiehe
Abstract: Bi2 Te3 based thermoelectric alloys have been commercialized in solid‐state refrigeration, but the poor mechanical properties restrict their further application. Nanotwins have been theoretically proven to effectively strengthen these alloys and could be sometimes constructed by strong deformation during synthesis. However, the obscure underlying formation mechanism restricts the feasibility of twin boundary engineering on Bi2 Te3 based materials. Herein, thorough microstructure characterizations are employed on a series of Bi0.4 Sb1.6 Te3+ δ alloys to systematically investigate the twins' formation mechanism. The results show that the twins belong to the annealing type formed in the sintering process, which is sensitive to Te deficiency, rather than the deformation one. The Te deficiency combined with mechanical deformation is prerequisite for constructing dense nanotwins. By reducing the δ below −0.01 and undergoing strong deformation, samples with a high density of nanotwins are obtained and exhibit an ultrahigh compressive strength over 250 MPa, nearly twice as strong as the previous record reported in hierarchical nanostructured (Bi, Sb)2 Te3 alloy. Moreover, benefitting from the suppressed intrinsic excitation, the average zT value of this robust material could reach near 1.1 within 30–250 °C. This work opens a new pathway to design high‐performance and mechanically stable Bi2 Te3 based alloys for miniature device development. Abstract : This study reports a great advance in strengthening (Bi, Sb)2 Te3 with high thermoelectric performance solely through nanotwins, an ultra‐high compressive strength over 250 MPa, nearly twice that of the previous record reported in hierarchical nanostructured (Bi, Sb)2 Te3 alloy. It starts from clarifying the formation mechanism of twins and then manipulating high‐density nanotwins to synergistically optimize thermoelectric and mechanical properties.